2021
DOI: 10.3390/ma14133464
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Ignition Height and Reaction Flame Temperature of PTFE/Al/Si/CuO with Different Mass Ratios of PTFE/Si

Abstract: Recent studies have shown that the energy release capacity of Polytetrafluoroethylene (PTFE)/Al with Si, and CuO, respectively, is higher than that of PTFE/Al. PTFE/Al/Si/CuO reactive materials with four proportions of PTFE/Si were designed by the molding–sintering process to study the influence of different PTFE/Si mass ratios on energy release. A drop hammer was selected for igniting the specimens, and the high-speed camera and spectrometer systems were used to record the energy release process and the flame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Cold pressing, where various molding pressures, molding rates, and molding periods affect the properties of the composite result, is the most crucial step in the preparation process. 27 Sun et al 28 investigated effect into how different holding times affected the properties of composites. The outcomes demonstrated that extending the holding period assisted in minimizing warpage of the composite sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Cold pressing, where various molding pressures, molding rates, and molding periods affect the properties of the composite result, is the most crucial step in the preparation process. 27 Sun et al 28 investigated effect into how different holding times affected the properties of composites. The outcomes demonstrated that extending the holding period assisted in minimizing warpage of the composite sheets.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the drop weight test was generally employed to examine the energy release characteristics, especially the impact-induced initiation characteristics of Al/ fluoropolymer RMs [17][18][19]. In the test, the impact energy can be obtained through the drop hammer height; however, the reaction proportion is usually low because the drop hammer has a quenching effect.…”
Section: Introductionmentioning
confidence: 99%
“…Ding [ 22 ] studied the impact energy release characteristics of PTFE/Al/CuO reactive materials with a self-designed energy release testing device, and the effects of particle size, the ratio of PTFE/Al and Al/CuO materials and sintering on the energy release ability of the reactive materials were investigated. Zou [ 23 ] studied the ignition height and reaction flame temperature of PTFE/Al/Si/CuO reactive materials with different mass ratios of PTFE/Si by a drop hammer impact test. Ran [ 24 ] quantitatively and qualitatively analyzed the energy release ability of six kinds of reactive materials formulations (PTFE/Al, PTFE/B, PTFE/Si, PTFE/Al/B, PTFE/Al/Si, and PTFE/Al/CuO) by using the drop weight system and a self-designed energy release testing device, and the results showed that the PTFE/Al/Si formulation had the best energy release ability.…”
Section: Introductionmentioning
confidence: 99%